Optical Properties Comparison of Carbon Nanodots Synthesized from Kangkung (Ipomoea aquatica) with Deep Frying and Roasting Techniques - Dwandaru, Wipsar Sunu Brams; Fauzi, Fika; Sari, Dyah Silviana; Sari, Emi Kurnia; Santoso, Iman; Suhendar, Haris (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2019)
Carbon nanodots (Cdots) have many unique properties such as luminescence that can be utilized in various fields. The purposes of this study are to synthesize Cdots from kangkung (Ipomoea aquatica) through frying and roasting techniques and compare the optical properties of the Cdots using UV-Vis, PL, and FTIR. Three stages of synthesizing process of Cdots, i.e.: preparing the kangkung powder (root, stem, leaf) and synthesizing the Cdots through frying and roasting techniques. Each part (root, stem, and leaf) was heated in an oven at 250 oC for 2 hours and mashed into powder. The frying method was done by frying 15 g of the powder in 120 ml oil for 5 minutes at 88 oC, filtered, and dissolved in n-hexane. In addition, the roasting method was done by frying the powder without oil as much as 15 g for 5 minutes, dissolved in 120 ml of distilled water, and then filtered. The UV-Vis characterization showed one absorbance peak for Cdots via frying and roasting techniques at 293 nm to 296 nm and 262 nm to 282 nm, respectively. The Cdots through frying and roasting techniques produce red and green luminescence, respectively. The FTIR characterization showed the presence of C=C and C=O functional groups, which are the core and surface state of the Cdots by frying technique, while the samples via roasting technique showed only the core. It can be concluded that the Cdots samples obtained from frying and roasting methods have different optical properties. The frying method produces Cdots with longer wavelength at the absorbance peak in the UV-Vis test compared to the roasting method. Moreover, the frying and roasting methods produce different color luminescence.